How reliable is the family expenditure survey? Trends in incomes and expenditures over time - James Banks; Paul Johnson (Institute for Fiscal Studies (IFS), 1998)
This book presents the results of the analysis discussed at a conference in July 1996 for users and providers of Family Expenditure Survey Data.
Keywords: 330